HUBUNGAN ANTARA JENIS KELAMIN USIA DAN BENTUK TELAPAK KAKI TERHADAP TINGKAT KESEIMBANGAN DINAMIS SISWA DI SDN 35 BILAH HULU - Kurnia Sari; Winara; Irsan; Husna Tambunan; Waliyul Siregar (STKIP Subang, 2025)
This study aims to determine the relationship between gender, age, and foot arch type with the dynamic balance of students at SDN 035 Bilah Hulu. This research employed a quantitative approach with a correlational method. The sample consisted of 107 students selected using total sampling technique. Data collection instruments used the dynamic balance test from “Test Your Physical Fitness” by C. Ashok. Data analysis included trend analysis, normality test, linearity test, correlation coefficient test, and hypothesis testing.The results showed that: there was no significant relationship between gender and dynamic balance (p = 0.851), there was no significant relationship between age and dynamic balance (p = 0.054; r = 0.187), and there was a significant relationship between foot arch type and dynamic balance (p < 0.001). Since the data were not normally distributed, non-parametric tests were used, namely the Mann-Whitney U Test, Spearman Rank, and Kruskal-Wallis Test.In conclusion, foot arch type has a significant influence on students’ dynamic balance, whereas gender and age do not show a meaningful relationship. These findings are expected to serve as a consideration in physical education activities, particularly in developing students' balance skills.